Reviews and Responses for Gradient-based smart predict-then-optimize framework for aircraft arrival scheduling problem - Lui, Go Nam; Demirel, Soner; Gianazza, David; Itoh, Eri; Sáez, Raúl (Journal of Open Aviation Science, 2025)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2024.7891